Moral, immoral, amoral : what is right and what is wrong? - Osho. (New York : St. Martin's Griffin, 2013)
In a global world, we are in search of universal values. In this book, Osho speaks directly to this contemporary search as he introduces us to a quest for values that make sense in the world we live in - a quest that goes far beyond moral codes of behavior and comes from an inner connectivity and oneness with existence.
Keywords: Osho International Foundation -- Doctrines; Spiritual life .